The Stunting Prevention Analysis (From Food Technology Training and Circular Economy Plan) - Indah Epriliati; Julius Runtu; Paini Sri Widyawati (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
Stunting is a latent problem, and Indonesia is still struggling to get out of this situation. It falls into the category of chronic stunting due to a lack of balanced nutritional intake. The motto